Program Penguatan Kapasitas Tendik SMK Sebagai Salah Satu Upaya Pendukung Penguatan Ekosistem Vokasi Di Provinsi Riau - Retno Tri Wahyuni; Muhammad Ihsan Zul; Hamid Azwar; Elva Susianti (Universitas Lancang Kuning, 2022)
Capacity Empowerment Program for Vocational High School Personnel is one part of the sosial corporate responsibilty (CSR) of PT Pertamina Hulu Rokan (PHR) in partnership with the PCR. This program is in order to support the strengthening of the vocational ecosystem in Riau Province which is in line with Governor Regulation Number 6 of 2022 concerning strengthening vocational education and training through partnerships with Industry, Business, and the World of Work. Capacity Empowerment Program for Vocational High School Personnel is packaged in the form of training and Microsoft Office certification. Through this program, it is hoped can support strengthening governance in vocational education units. A total of 144 people from 42 vocational schools signed up for this program. After going through the selection process, 26 participants from 25 vocational schools were selected. The series of programs run according to the planned schedule. Feedback on the program indicated that participants experienced increased knowledge and skills regarding Microsoft Office. All training participants were also declared competent in the Junior Office Operator scheme and received a certificate from the National Professional Certification Agency (BNSP).